JUDICIAL REASONING IN MARRIAGE DISPENSATION AT THE TAKENGON SYAR'IYAH COURT: A Critical Analysis of Legal Pluralism and The Paradox of Child Protection - Apriliansyah, Muhammad Akmal; Gulo, Azhar Nur Mawaddah; Subhan, Bentara (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the judicial reasoning model in granting marriage dispensation at the Takengon Syar'iyah Court through a critical analysis of Decision Number 185/Pdt.P/2024/MS.Tkn. Using a socio-legal approach with legal pluralism and maqashid al-syariah frameworks, this research reveals that judges employ a three-stage hierarchical reasoning pattern: formal-procedural, social fact verification, and Islamic law substantive justification. The findings indicate that positive law (Law No. 16/2019 and PERMA No. 5/2019) functions as an initial barrier and procedural legitimizer, while Islamic law, particularly the fiqh maxim dar'u al-mafasid muqaddamun 'ala jalb al-mashalih (preventing harm takes precedence over bringing benefit), serves as a substantive problem-solver. Local socio-cultural realities, especially unplanned pregnancy and family honor concerns, act as triggering factors that are subsequently framed as